Early stages of ocean formation between Australia and Antarctica - Vanda M. Sergeeva; German L. Leitchenkov (Записки Горного института, 2025)
The paper deals with geodynamic reconstructions of Australia and Antarctica (using the GPlates program) 79, 68-61, 48, 44, and 40 Ma based on the comparison of conjugate single-age magnetic anomalies. The relevance of the present study is determined by the increased scientific interest in the problems of Gondwana break-up and the influence of lithospheric block tectonics on the processes of riftogenesis and ocean opening. The early stage of oceanic opening between Australia and Antarctica is characterised by a series of distinct linear magnetic anomalies. Oceanic spreading occurred in an ultra-slow to slow regime with rates of 20-26 mm/year between 33o and 21u anomalies (80-48 Ma) and 40 mm/year between 21u and 18o anomalies (48-40 Ma). According to the studies, there is a clear correlation between the change in spreading rate and the position of the rotation poles. Between 80 and 48 Ma, the rotation pole was located to the west, in the Kerguelen Plateau region, and Australia shifted westward relative to Antarctica. About 48 million years ago, the rate of seafloor spreading almost doubled (from ultra-slow to slow), and Australia began to migrate northwards. The rotation pole was near the southern edge of Tasmania and continued to move southeast towards the Pacific Ocean. The separation of Australia and Antarctica was associated with the advance of the spreading axes of the Indian and Pacific oceans towards each other, with orthogonal inter-section of the ancient lithospheric blocks of the two continents, and was determined by the geometry of the marginal rift structures.